AB1310 Practical use of ultrasonography detects residual joint synovitis in patients with rheumatoid arthritis achieving clinical remission in daily clinical setting. (23rd January 2014) - Seto, Y.; Inoue, E.; Taniguchi, A.; Momohara, S.; Yamanaka, H.
Abstract : Background: Patients with rheumatoid arthritis (RA) in clinical remission may still have evidence of synovitis detectable by ultrasonography (US), which is associated with structural damage. It has been reported that positive power Doppler (PD) activity is still detectable by US in metacarpophalangeal joints and wrist of dominant hand even in patients in clinical remission defined by more stringent criteria (1). Objectives: To assessed the presence of residual synovitis with PD activity in any peripheral joints of interest detected by US in RA patients achieving clinical remission in daily clinical setting. Methods: Any peripheral joints including bilateral wrist, finger, glenohumeral, knee, ankle and metatarsophalangeal joints were scanned by US in daily outpatient clinic when confirmation of physical examination was needed, within eight weeks after clinical evaluation such as joint counts, inflammatory markers, composite disease activity scores, and physical function. Clinically obvious swollen or non-swollen joints were excluded for US examination. Among the patients, those who achieved clinical remission defined by DAS28 or new ACR/EULAR definitions were retrospectively collected from IORRA database of Tokyo Women's Medical University, and the frequency of positive intra-capsular PD signal was evaluated. Results: US scan of at least one joint was performed in 92 patients (female 78%, median age 57.6 year and duration 5.0 year) and numbers (%) of patients fulfilling remission in DAS28, CDAI, SDAI or Boolean definition were 46 (50.0), 20 (21.7), 23 (25.0) and 20 (21.7), respectively. Positive PD signal was present in 24/46, 11/20, 11/23 and 12/20 patients, in which PD activity was even detected in joints that the physician assumed to be non-swollen among 7/46, 2/20, 2/23 and 3/20 patients regarding 28 joints, and in 11/46, 5/20, 6/23 and 6/20 patients when including bilateral feet, respectively. Conclusions: Imaging assessment on even selected joints of interested would be advisable when strictly targeting remission. References: Saleem B, Brown AK, Keen H, Nizam S, Freeston J, Wakefield R, Karim Z, Quinn M, Hensor E, Conaghan PG, Emery P. Should imaging be a component of rheumatoid arthritis remission criteria? A comparison between traditional and modified composite remission scores and imaging assessments. Ann Rheum Dis 2011; 70: 792-798. Disclosure of Interest: Y. Seto: None Declared, E. Inoue: None Declared, A. Taniguchi: None Declared, S. Momohara: None Declared, H. Yamanaka Grant/Research support from: IORRA study is supported from 40 pharmaceutical companies; Asahikasei Kuraray Medical Co., Ltd., Abbott Japan Co., Ltd., Asahikasei Pharma Corporation, AstellasPharma Inc., AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Daiichi Fine Chemical Co., Ltd., Daiichi Sankyo Co., Ltd., Dainippon Sumitomo Pharma Co., Ltd., Eisai Co., Ltd., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K., Japan Tobacco Inc., Kaken Pharmaceutical Co., Ltd., Kissei Pharmaceutical Co., Ltd., Kowa Pharmaceutical Co.Ltd., Maruho Co., Ltd., Mitsubishi Chemical Medience Corporation, Mitsubishi Tanabe Pharma Corporation, Mochida Pharmaceutical Co. Ltd., MSD K.K., Mundipharma K.K., Nippon Chemiphar Co., Ltd., Nippon Shinyaku Co., Ltd., Novartis Pharma K.K., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Sanwa Kagaku Kenkyusho Co., Ltd., Sekisui Medical Co., Ltd., Shionogi Co., Ltd., Taishotoyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co. LTD., Teijin Pharma Limited, Torii Pharmaceutical Co., Ltd., UCB Japan Co. Ltd., ZERIA Pharmaceutical Co., Ltd., Consultant for: Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB.